2007
DOI: 10.1002/jbt.20189
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the antimicrobial activity of ebselen: Role of the yeast plasma membrane H+‐ATPase

Abstract: Ebselen (2-phenyl-1,2-benzisoselenazol-3(2H)-one) is a selenium-containing antioxidant demonstrating anti-inflammatory and cytoprotective properties in mammalian cells and cytotoxicity in lower organisms. The mechanism underlying the antimicrobial activity of ebselen remains unclear. It has recently been proposed that, in lower organisms like yeast, the plasma membrane H+-ATPase (Pma1p) could serve as a potential target for this synthetic organoselenium compound. Using yeast and bacteria, the present study fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 43 publications
(59 reference statements)
5
66
0
Order By: Relevance
“…It has been previously reported that ebselen exhibits both glutathione peroxidase activity and antioxidant activity and that ebselen inhibits several redox-sensitive enzymes such as constitutive endothelial nitric oxide synthase, lipoxygenases, nicotinamide adenine dinucleotide phosphate oxidase, and other activities (Table 2 and [29,[38][39][40][41][42][43]). Furthermore, organoselenium compounds in the form of seleninic acids can couple with thiols on catalytically important cysteine residues (e.g., of phosphotyrosine phosphatase), resulting in enzyme inhibition [44].…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that ebselen exhibits both glutathione peroxidase activity and antioxidant activity and that ebselen inhibits several redox-sensitive enzymes such as constitutive endothelial nitric oxide synthase, lipoxygenases, nicotinamide adenine dinucleotide phosphate oxidase, and other activities (Table 2 and [29,[38][39][40][41][42][43]). Furthermore, organoselenium compounds in the form of seleninic acids can couple with thiols on catalytically important cysteine residues (e.g., of phosphotyrosine phosphatase), resulting in enzyme inhibition [44].…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy in IC 50 s is likely due to the difference in the strains tested, as different strains may carry different levels of the drug target, which, in this case, is the quorumsensing membrane receptor AgrC. Ebselen, as reported by Chan et al (22), can inhibit S. aureus with an IC 50 of approximately 4.3 M, which compares well with the results of our experiments, which found an IC 50 of 1.3 M. To the best of our knowledge, there are no reports on the antimicrobial activity of verteporfin against either planktonic cultures or preformed biofilms of S. aureus. In our experiments, verteporfin had significant antimicrobial activity with an IC 50 of 1.6 M. Using another photoactive compound unrelated to verteporfin (methylene blue), Tubby et al (23) demonstrated that the photodynamic inactivation of bacteria remains a viable antimicrobial strategy, especially for localized infections.…”
Section: Resultsmentioning
confidence: 94%
“…In mammals, they include important regulatory proteins such as the NF-B transcription factor (53), signal transduction kinases such as c-Jun N-terminal kinase (54) and protein kinase C (55), and Na ϩ /K ϩ -ATPases (56). In yeast, ebselen, a synthetic organoselenium compound converted into a selenol in vivo, was shown to inhibit the activity of the plasma membrane H ϩ -ATPase (Pma1p), involved in the regulation of intracellular pH and essential for growth (57). Ebselen was also shown to react with multiple cysteine residues of various other yeast proteins (58).…”
Section: Discussionmentioning
confidence: 99%